2021
DOI: 10.1051/e3sconf/202131701075
|View full text |Cite
|
Sign up to set email alerts
|

Community-Based Adaptation: Challenge and Opportunity in Indonesia

Abstract: Climate change is a serious problem mostly caused by human activities but the impacts are felt by all creatures in the word. These conditions are worsened by the rise of ‘dirty industries’ that exceed the environmental carrying capacity. Many studies had showed that people need to do something to cut climate change from individual to state scale. Therefore, community plays an important role to climate change program’s success. It is known as community-based adaptation (CBA). CBA combines indigenous knowledge, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…Based on the results of the research above, it can be concluded that in addition to several successful implementations of Proklim in a number of regions (Muttaqin et al, 2019) (Qomariah et al, 2021) (Priyanto et al, 2020), the study also found various challenges, especially the response of the community in carrying out the Proklim. Mainly related to community involvement in adaptation or how people find solutions to climate change and environmental damage caused by a changing climate that affects their ability to meet their daily needs.…”
Section: The Current Development Of Proklimmentioning
confidence: 94%
“…Based on the results of the research above, it can be concluded that in addition to several successful implementations of Proklim in a number of regions (Muttaqin et al, 2019) (Qomariah et al, 2021) (Priyanto et al, 2020), the study also found various challenges, especially the response of the community in carrying out the Proklim. Mainly related to community involvement in adaptation or how people find solutions to climate change and environmental damage caused by a changing climate that affects their ability to meet their daily needs.…”
Section: The Current Development Of Proklimmentioning
confidence: 94%